The role and importance of mathematics in innovation : proceedings of the Forum "Math-for-Industry" 2015 ; Bob Anderssen, Philip Broadbridge, Yasuhide Fukumoto, Naoyuki Kamiyama, Yoshihiro Mizoguchi, Konrad Polthier, Osamu Saeki, editor. - Anderssen, R. S.; Broadbridge, Philip, 1954-; Fukumoto, Yasuhide; Kamiyama, Naoyuki; Mizoguchi, Yoshihiro; Polthier, Konrad; Saeki, Osamu, 1955- (Mathematics for industry (Springer (Firm)) ;, 2016)
This book is a collection of papers presented at the "Forum Math-for-Industry 2015" for which the unifying theme was "The Role and Importance of Mathematics in Innovation", held at the Institute of Mathematics for Industry, Kyushu University, October 26-30, 2015. The theme highlights two key roles that mathematics plays in supporting innovation in science, technology, and daily life, namely, needs-based and idea-based. For the former, mathematics assists with sorting through the possibilities and putting matters on a more rigorous foundation, and for the latter, mathematical models of the possible implementations play a key role. The book gives excellent examples of how mathematics assists with stimulating innovation and, thereby, highlights the importance and relevance of the concept Mathematics_FOR_Industry. The contents of this volume address productive and successful interaction between industry and mathematicians, as well as the cross-fertilization and collaboration that result when mathematics is involved with the advancement of science and technology.